Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1523/jneurosci.0392-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Panglial Gap Junctional Communication is Essential for Maintenance of Myelin in the CNS

Abstract: In this study, we have investigated the contribution of oligodendrocytic connexin47 (Cx47) and astrocytic Cx30 to panglial gap junctional networks as well as myelin maintenance and function by deletion of both connexin coding DNAs in mice. Biocytin injections revealed complete disruption of oligodendrocyte-to-astrocyte coupling in the white matter of 10-to 15-d-old Cx30/Cx47 double-deficient mice, while oligodendrocyte-to-oligodendrocyte coupling was maintained. There were no quantitative differences regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(94 citation statements)
references
References 37 publications
3
90
0
Order By: Relevance
“…In addition, double knockouts for the astrocyte hemichannels Cx43 and Cx30 develop widespread white matter pathology with impairment of oligodendrocyte maturation and myelin vacuolation, whereas mice with astrocyte-targeted loss of Cx43 or Cx30-null mice do not show signs of abnormal myelination (85)(86)(87). Double knockouts affecting both oligodendrocyte and astrocyte hemichannels (Cx47/ Cx30) develop a progressive phenotype with early vacuolization of myelin with microgliosis, astrogliosis, motor impairment, and early death (88). Glial fibrillary acidic protein (Gfap)-Cre-mediated depletion of astrocyte Cx43 in oligodendrocyte Cx32-null mice revealed a similar phenotype characterized by severe myelin vacuolization, astrocyte loss, and early death (89).…”
Section: Mct1mentioning
confidence: 99%
“…In addition, double knockouts for the astrocyte hemichannels Cx43 and Cx30 develop widespread white matter pathology with impairment of oligodendrocyte maturation and myelin vacuolation, whereas mice with astrocyte-targeted loss of Cx43 or Cx30-null mice do not show signs of abnormal myelination (85)(86)(87). Double knockouts affecting both oligodendrocyte and astrocyte hemichannels (Cx47/ Cx30) develop a progressive phenotype with early vacuolization of myelin with microgliosis, astrogliosis, motor impairment, and early death (88). Glial fibrillary acidic protein (Gfap)-Cre-mediated depletion of astrocyte Cx43 in oligodendrocyte Cx32-null mice revealed a similar phenotype characterized by severe myelin vacuolization, astrocyte loss, and early death (89).…”
Section: Mct1mentioning
confidence: 99%
“…To examine whether these changes occur in vivo, we performed whole-cell patch clamp experiments in brain slices (Figs 6 and 7). Patch pipette solutions contained CsCl to suppress K þ currents and the gap junction blocker carbenoxolone to electrically isolate the patched cell from the panglial network 21 . Control experiments with transfected HEK cells confirmed that carbenoxolone did not affect ClC-2 currents ( Supplementary Fig.…”
Section: Mlc1 and Glialcam Mouse Models Exons 2 And 3 Of The Mlc1mentioning
confidence: 99%
“…However, the mechanisms underlying their energy metabolism, in particular the pathways involved in energy metabolite uptake and trafficking remain unidentified. Functional tests have shown that astrocytes and oligodendrocytes are connected by gap junctions to form panglial networks (Griemsmann et al, 2014;Ransom and Giaume, 2013;Tress et al, 2012). Moreover, astroglial connexin channels (gap junction channels and hemichannels) are permeable to glucose derivatives (2-NBDG) in both in vitro and ex vivo models (Blomstrand and Giaume, 2006;Retamal et al, 2007a), thus they provide the basis to form metabolic intercellular networks (Rouach et al, 2008).…”
Section: Inhibition Of Hemichannel Activity Impacts Opc Proliferationmentioning
confidence: 99%
“…This dependence might partly explain why OPCs are more vulnerable to oxygen-glucose deprivation than oligodendrocytes (Fern and Moller, 2000;Ziabreva et al, 2010). Moreover, likely due to deficient Cx47-based hemichannel properties, Cx47-null mice exhibit decreased oligodendroglial lineage cell numbers at P14, but gene knockdown does not influence myelination in adult mice (Tress et al, 2012). Finally, abnormal connexin expression is involved in limiting OPC recruitment and consequent remyelination failure in multiple sclerosis patients and in autoimmune encephalomyelitis mice (a model of multiple sclerosis) (Markoullis et al, 2012a(Markoullis et al, ,b, 2014.…”
Section: Inhibition Of Hemichannel Activity Impacts Opc Proliferationmentioning
confidence: 99%
See 1 more Smart Citation